Molecular characterization of misidentified Plasmodium ovale imported cases in Singapore. (December 2015) - Chavatte, Jean-Marc; Tan, Sarah; Snounou, Georges; Lin, Raymond
Abstract Background Plasmodium ovale, considered the rarest of the malaria parasites of humans, consists of two morphologically identical but genetically distinct sympatric species, Plasmodium ovale curtisi andPlasmodium ovale wallikeri . These parasites resemble morphologically toPlasmodium vivax with which they also share a tertian periodicity and the ability to cause relapses, making them easily misidentified asP. vivax .Plasmodium ovale infections are rarely reported, but given the likelihood of misidentification, their prevalence might be underestimated. Methods Morphological and molecular analysis of confirmed malaria cases admitted in Singapore in 2012–2014 detected nine importedP. ovale cases that had been misidentified asP. vivax . SinceP. ovale had not been previously officially reported in Singapore, a retrospective analysis of available, frozen, archival blood samples was performed and returned two additional misidentifiedP. ovale cases in 2003 and 2006. These elevenP. ovale samples were characterized with respect to seven molecular markers (ssrRNA, Potra, Porbp2, Pog3p, dhfr -ts, cytb, cox1 ) used in recent studies to distinguish between the two sympatric species, and to a further three genes (tufa, clpC andasl ). Results The morphological features ofP. ovale and the differential diagnosis withP. vivax were reviewed and illustrated by microphotographs. The genetic dimorphism betweenP. ovale curtisi andP. ovale wallikeri was assessed by ten molecular markers distributed across the three genomes of the parasite (Genbank KP050361-KP050470). The data obtained for seven of these markers were compared with those published and confirmed that bothP. ovale species were present. This dimorphism was also confirmed for the first time on: (1) two genes from the apicoplast genome (tufA andclpC genes); and, (2) theasl gene that was used for phylogenetic analyses of otherPlasmodium species, and that was found to harbour the highest number of dimorphic loci between the twoP. ovale species. Conclusion MisidentifiedP. ovale infections are reported for the first time among imported malaria cases in Singapore. Genetic dimorphism betweenP. ovale curtisi andP. ovale wallikeri was confirmed using markers from the parasites' three genomes. The apparent increase of importedP. ovale since 2012 (with yearly detection of cases) is puzzling. Given decrease in the overall number of malaria cases recorded in Singapore since 2010 the 'resurgence' of this neglected species raises public health concerns.